Compliance em micro e pequenas empresas: a adoção de programas de integridade como instrumento de combate à corrupção - Santin, Carlos Afonso Rigo (2024)
The dissertation studies compliance in Brazil and the world, with emphasis on the adoption of Integrity programs in small and micro companies. The problem to be solved is: which elements are present in integrity programs as instruments for greater efficiency of the objective of combating corruption in micro and small companies in Brazil? The first chapter presents the phenomenon of corruption, its historical, social, legal and economic; landmark cases of combating corruption; the damage caused by this phenomenon and the benefits of combating it. In the second chapter, the main laws and treaties relating to combating corruption, especially in micro and small companies, with emphasis on the Anti-Corruption Law (Law 12,846/2013), the Bidding and Contracts Law Administrative (Law 14,133/21), UN and OECD conventions, the Joint Ordinance in 2,279/2015, Decree 11,129/22, in addition to SEBRAE and CADE manuals. The third chapter addresses the practical case of creating the Integrity Program in a small company based in the municipality of Passo Fundo (RS): "TopoMen Soluções Geoespaciais", active in the area of topography and georeferencing. This chapter presents the difficulties and challenges faced in the case of TopoMen, as well as recommendations and lessons that can serve for other companies that want to do the same. In methodological terms, the research uses the method deductive, in addition to practical case analysis. The main source of research is bibliographical, with a multidisciplinary approach. It is concluded that integrity programs are important instruments to combat corruption - private companies, of all sizes, must keep up with the evolution of legislation and the globalized market, adopting a culture business of integrity, ethics and transparency.